Consideration under the English Law and the Malaysian Contracts Act 1950: a comparative study / Zulkifli Zabidin - Zabidin, Zulkifli (Faculty of Law, 1987)
Consideration is one of the most important elements to constitute a valid and enforceable contract. Being so, it has caused confusion among the law students and lawyers alike. Provision of different laws has worsen the situations and this is especially so in Malaysia. The contract law of Malaysia, which is governed by the Malaysia Contracts Act 1950. As a statutory law drafted similar to that of the Indian Contract Act. As far as the Indian Contract Act is concerned, one famous author, Sir Frederick Pollock, has said that the characteristic of that Act was that it was a code of the English Law.